The bioenergetics of optimal performances in middle-distance and long-distance track running - Ward-Smith, A. J. (Journal of Biomechanics, 1999)
Aspects of anaerobic and aerobic energy conversion are investigated using a mathematical model of running in conjunction with world-record statistics. Analysis of the data shows that over distances from 1500 to 10,000 m the anaerobic energy utilised is constant and independent of running distance. This result is consistent with the view that the full potential of the anaerobic capacity is available for conversion during extended periods of running; the opinions of Gollnick and Hermansen (1973) and Peronnet and Thibault (1989) that the anaerobic energy contribution declines with race duration are not corroborated. The analysis supports the finding of Peronnet and Thibault (1989) that, for running times below about T=420 s, the maximum sustainable aerobic power is constant, and that for larger T it then declines progressively. The present analysis shows it falls by some 4.5% over 10,000 m, T1600 s, indicating that in establishing current world records at 5000 and 10,000 m athletes did not rely solely on glycogen as the source of aerobic metabolism; limited use was made of free fatty acids. For elite male runners, the anaerobic capacity and maximal aerobic power are evaluated as 1570 J/kg and 27.1 W/kg, respectively.